2020
DOI: 10.2139/ssrn.3567419
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Economic Crisis: The Nigerian Experience and Structural Causes

Abstract: We are in the midst of the worst recession since the global financial crisis. The economic downturn in Nigeria was triggered by a combination of declining oil price and spillovers from the Covid-19 outbreak, which not only led to a fall in the demand for oil products but also stopped economic activities from taking place when social distancing policies were enforced. The government responded to the crisis by providing financial assistance to businesses, not to households, that were affected by the outbreak. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 49 publications
(19 reference statements)
0
81
0
1
Order By: Relevance
“…This Russian-perspective analysis of all the COVID19 anti-epidemic, administrative, and organizational measures revealed that several bottleneck inefficiencies. In other countries, ranging from Nigeria to Italy, similar health system vulnerabilities were exposed which require an effective solution in the medium term [40][41][42][43][44]. We proposed several measures aimed at ensuring the readiness of the administrative, sanitary, and anti-epidemic and for preparing the healthcare facilities for epidemics of infectious diseases: architectural-planning and construction-household solutions; modular medical equipment; organizing mobile diagnostic medical laboratories; the development of sanitary and hygienic recommendations for the self-isolation regime; medical and non-medical workforce reserve; reliability of information support in the media; international assistance to countries experiencing the most considerable difficulty in fighting the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This Russian-perspective analysis of all the COVID19 anti-epidemic, administrative, and organizational measures revealed that several bottleneck inefficiencies. In other countries, ranging from Nigeria to Italy, similar health system vulnerabilities were exposed which require an effective solution in the medium term [40][41][42][43][44]. We proposed several measures aimed at ensuring the readiness of the administrative, sanitary, and anti-epidemic and for preparing the healthcare facilities for epidemics of infectious diseases: architectural-planning and construction-household solutions; modular medical equipment; organizing mobile diagnostic medical laboratories; the development of sanitary and hygienic recommendations for the self-isolation regime; medical and non-medical workforce reserve; reliability of information support in the media; international assistance to countries experiencing the most considerable difficulty in fighting the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Only few African countries used large public funds to mitigate the effects of the coronavirus pandemic. Nigeria announced a NGN3.5trillion (US$9.1bn) coronavirus relief fund (Ozili, 2020). Gambia announced a D500million (US$9.8m) coronavirus relief fund.…”
Section: Angolamentioning
confidence: 99%
“…In Nigeria, COVID-19 case was officially identified on 27 th February 2020 and few more cases was identified after then (Effiong, et al 2020). The consequences of COVID-19 on the economy and financial markets in Nigeria are: economic lockdown of major cities (Abuja, Lagos, Ogun states) on 30 th March 2020 leading to economic loss especially for daily income earners from small-medium scale businesses, withdrawal of money by investors from the market and fall in oil prices (Ozili, 2020) and on the global economiy, the impact of the COVID-19 cannot also be overemphasized (Mckibbin and Fernando, 2020) because it can lead to huge external debt of any country.…”
Section: Introductionmentioning
confidence: 99%